Neurocan Inhibits Semaphorin 3F Induced Dendritic Spine Remodeling Through NrCAM in Cortical Neurons - Mohan, Vishwa; Wyatt, Elliott V.; Gotthard, Ingo; Phend, Kristen D.; Diestel, Simone; Duncan, Bryce W.; Weinberg, Richard J.; Tripathy, Ashutosh; Maness, Patricia F. (Frontiers in Cellular Neuroscience, 2018)
Neurocan is a chondroitin sulfate proteoglycan present in perineuronal nets, which are associated with closure of the critical period of synaptic plasticity. During postnatal development of the neocortex dendritic spines on pyramidal neurons are initially overproduced, later they are pruned to achieve an appropriate balance of excitatory to inhibitory synapses. Little is understood about how spine pruning is terminated upon maturation. NrCAM (Neuron-glial related cell adhesion molecule) was found to mediate spine pruning as a subunit of the receptor complex for the repellent ligand Semaphorin 3F (Sema3F). As shown here in the postnatal mouse frontal and visual cortex, Neurocan was localized at both light and electron microscopic level to the cell surface of cortical pyramidal neurons and was adjacent to neuronal processes and dendritic spines. Sema3F-induced spine elimination was inhibited by Neurocan in cortical neuron cultures. Neurocan also blocked Sema3F-induced morphological retraction in COS-7 cells, which was mediated through NrCAM and other subunits of the Sema3F holoreceptor, Neuropilin-2 and PlexinA3. Cell binding and ELISA assays demonstrated an association of Neurocan with NrCAM. Glycosaminoglycan chain interactions of Neurocan were required for inhibition of Sema3F-induced spine elimination, but the C-terminal sushi domain was dispensable. These results describe a novel mechanism wherein Neurocan inhibits NrCAM/Sema3F-induced spine elimination.